FORMATION OF MARKETING STRATEGY OF EDUCATIONAL ORGANIZATION (Scientific journal of the Fergana State University, 2024)
The article discusses the marketing strategy of an educational organization. Features of development of marketing strategy are revealed. The basic definitions, types of marketing strategy are described. The basic definitions, educational services, stages of development of marketing strategy are described.